The Effect of Early Diagenesis in Methanic Sediments on Sedimentary Magnetic Properties: Case Study From the SE Mediterranean Continental Shelf - Amiel, Nitai; Shaar, Ron; Sivan, Orit (Frontiers in Earth Science, 2020)
Microbial respiration in marine sediment can affect the magnetic properties of the sediment through a complicated interplay between reductive dissolution and authigenic precipitation of iron-bearing magnetic minerals. However, a direct link between the main diagenetic zones in the upper sedimentary column and sedimentary magnetic properties using high resolution multi parameter profiles has been demonstrated only in few studies. Here, we directly correlate early diagenetic processes and sedimentary magnetism using a composite high-resolution sedimentary record of pore water chemistry, solid phase chemical measurements and mineral-magnetic parameters. Measurements along the profiles include the entire redox cascade, from the water-sediment interface, down through the deep methanic zone, on a six-meter sediment core collected from the Southern Eastern Mediterranean continental shelf. The uppermost part of the sediment core, associated with oxic, nitrous, manganous, ferruginous, and sulfate reduction zones, is characterized by high ferrous iron and sulfate concentrations and high values of the measured magnetic parameters [susceptibility, Isothermal remanent magnetization (IRM) and Anhysteretic remanent magnetization (ARM)]. This layer is underlain by a sulfate-methane transition zone (SMTZ) that shows a significant decrease in magnetic parameters due to the dissolution of magnetic minerals. Below the SMTZ, the methanic zone has been assumed to be magnetically inactive under steady-state conditions. However, we observe in the upper methanic zone an increase in microbial iron reduction, coupled to an abrupt increase in magnetic parameters. Our data indicate that the observed increase in the magnetic signal is related to the precipitation of authigenic magnetic minerals. These diagenetic changes should be considered when interpreting paleomagnetic data, and highlight the potential to use high-resolution magnetic data as a proxy for identifying diagenetic processes.